Read my lips: the role of information transmission in multilateral reform design - Silvia Marchesi; Laura Sabani; Axel Dreher (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
We focus on the role that the transmission of information between a multilateral (e.g., the IMF) and a country has for optimal (conditional) reform design. The main result is that the informational advantage of the country must be strictly greater than the advantage of the multilateral in order to increase a country's discretion in the choice of the policies to be implemented (country ownership). To the contrary, an increase in the conflict of interests between the multilateral and the country may lead the multilateral to leave more freedom in designing reforms, which is at odds to what is commonly argued. Our empirical results provide support to the idea that the IMF follows an optimal allocation rule of control rights over policies, leaving the recipient countries more freedom whenever their local knowledge appears to be crucial for designing more adequate reforms.
Keywords: C23; D82; F33; N2; 330; IMF conditionality; delegation; communication; ownership; panel data